2020
DOI: 10.1063/5.0012409
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sulfur on the melt dynamics of glass forming Ti75Ni25−xSx

Abstract: Substitution of Nickel by Sulfur leads to bulk metallic glass formation in eutectic Ti 75 Ni 25 . In order to understand the improved glass forming ability, a detailed analysis of the melt dynamics was performed. We measured the density, the viscosity, and the self-diffusion of Ti 75 Ni 25 x S x (x ¼ 0, 5, 8) melts as a function of temperature. Moreover, the viscosity was measured under reduced gravity conditions to benchmark ground-based data. The self-diffusion coefficients were probed by incoherent, quasi-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…[36]). The activation energy in Pd-Ni-S melts corresponds to about the half of the activation energy in Ti 75 Ni 20 S 5 melts with E A = 657 meV [14].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…[36]). The activation energy in Pd-Ni-S melts corresponds to about the half of the activation energy in Ti 75 Ni 20 S 5 melts with E A = 657 meV [14].…”
Section: Resultsmentioning
confidence: 97%
“…Within the ternary Pd-Ni-S system, Pd 37 Ni 37 S 26 represents the best glass former with a critical casting thickness of 2 mm, whereas Pd 31 Ni 42 S 27 exhibits the best thermal stability against crystallization upon heating from the glassy state [12,13]. A recent study on Ti-Ni-S melts reveals that S-addition affects the melt dynamics differently [14] than element addition in Ni-P-based melts [8]. Here the Ti/Ni self-diffusion and the packing fraction decrease simultaneously upon S-addition.…”
Section: Introductionmentioning
confidence: 99%
“…In the Ti-Ni-S melt, the melt dynamics slow down with increasing sulfur content, as a result of potential covalent-like interactions involved. 14 Despite the chemical similarity (e.g., Ti-Nb forms a completely miscible binary phase diagram 39 ), the melt dynamics does not seems to be affected by the sulfur addition for Ni 58 Nb 39 S 3 . However, a distinct difference is that overall the sulfur concentration in the studied Ti-Ni-S alloys is higher, in the range of 5 − 8 at.…”
Section: Article Pubsaiporg/aip/apmmentioning
confidence: 99%
“…% has indeed been observed, whereas in the Pd-Ni-S alloy melts, where the sulfur content is considerably higher, the diffusive dynamics of Ni depends only very weakly on the sulfur concentration. 14,15 This indicates that the mechanisms of improved GFA upon sulfur addition can be different in different alloy systems.…”
mentioning
confidence: 99%
“…Minor additions of certain elements are added to a known alloy composition, changing the crystallization sequence and kinetics. In the last years, our group discovered sulfur as a constituent in BMGs [16][17][18][19][20], allowing for a large variety of new approaches for alloy development. It was also found that additions of sulfur significantly improve the thermal stability of Vit105 upon heating [16].…”
Section: Introductionmentioning
confidence: 99%